An investigation on tapered wings with leading edge tubercles - Zhang, Yongjie (2017)
An experimental study was conducted to examine the flow around swept tapered wings with leading edge protuberances. Particle Imaging Velocimetry, a non-intrusive flow visualisation technique was conducted in a water tunnel. 2 wings with SD7032 airfoil profile and a mean aerodynamic chord of 82.15mm, and a sweep angle of 30° were tested at angles of attack (α) of 0°,10°, and 20°. Both wings, one with a straight leading edge and the other one with leading edge protuberances of amplitude equal to 0.12 of the local chord (c) and wavelength equal to 0.47 mean aerodynamic chord, were tested at Reynolds number 1.4×104 . After processing the images, flow phenomenon such as inhibition of span wise flow, much more energetic wake vortices are seen in the cross-stream images, whereas early onset of separation and flow reattachment at high angles of attack in the trough region and can be seen in the streamwise images. In addition, an experiment was designed to investigate the effects of these protuberances on rotor blades. The designs of the blades mimicked the actual rotor blades that were used in a UH-1H Bell helicopter. In total, 4 configurations of rotor blades were designed using Solid Works, one with straight leading edge, and the 3 others with varying amplitudes(A) and wavelength(λ) for the leading edge protuberances, (A=0.05c λ = 0.25c, A=0.15c λ = 0.25c, A=0.05c λ = 0.125c). In addition, 2 hubs of fixed AOA of 0° and 15° were also designed, for the blades to be mounted on the motor and also to test the performance of rotor blades at different flow regimes. 3 different speeds will be tested, 400 revolutions per minute (RPM), 600 RPM, 800 RPM, while the whole assembly is to be placed onto a force transducer, and data of the lift are collected after reaching steady state to determine the aerodynamic performance of the rotor blades with leading edge protuberances.